Smoking enhances bone loss in anterior teeth in a Brazilian population: a retrospective cross-sectional study - Fernando Renó de Lima; João Batista Cesar-Neto; Dimas Renó de Lima; Warley David Kerbauy; Getulio Rocha Nogueira-Filho (Sociedade Brasileira de Pesquisa Odontológica, 2008)
The aim of the present study was to radiographically evaluate the effect of smoking on bone loss resulting from chronic periodontitis. Periapical radiographs were analyzed of 80 patients with chronic periodontitis (40 current or former smokers and 40 never-smokers) that attended a private periodontal practice. The smokers or former-smokers with a minimum consumption of 10 cigarettes/day for a period of over 10 years were selected. Interproximal radiographic bone loss was considered as the distance between the cementum-enamel junction and the alveolar bone crest. Bone loss for smokers was higher than that observed in never-smokers (p < 0.05) (3.33 ± 1.09 mm and 2.24 ± 0.76 mm; mean ± standard deviation for smokers and non-smokers, respectively). When each region of the mouth was comparatively evaluated, it was observed that the smokers' incisors presented the highest bone loss when compared with the other groups of teeth (p < 0.01). Within the limits of the present investigation it can be concluded that smoking enhances the bone loss resulting from periodontitis and that the incisors are the teeth most affected.